Determinants of the prevalence and location of musculoskeletal pain in elite Para athletes - Zwierzchowska, A.; Gawel, E.; Rosolek, B. (Medicine, 2022)
The tendency for musculoskeletal complaints, injuries, and traumas remains significant among Para athletes. The aim of the study was to identify and verify the variables that impact the incidence and location of musculoskeletal pain in elite athletes with disabilities. It was assumed, that the type of disability and not the type of sport, or the type of injuries and traumas is the crucial determinant of the prevalence and location of musculoskeletal pain in Para athletes. A direct-participatory observation method was used in the study including both subjective (surveys questionnaires) and objective (anthropometric) methods of assessment. The study included 35 male and female elite Para athletes from the Polish national team (sitting volleyball [SG1: n = 21], para swimming [SG2 = 14]). Both groups of Para athletes mostly reported pain in the neck (37%), and the lower back (34%). The Spearman`s rank-order correlation showed several large inversely proportional relationships between somatic parameters and the values in the Nordic Musculoskeletal Questionnaire from the last 7 days (NMQ-7) for SG2 and some moderate to large correlations between body adiposity index (BAI) and the prevalence of injuries, the total number of rehabilitation sessions, the number of humeral joint and fingers rehabilitation sessions, breaks from training over 4 weeks in SG1. In both groups relationships were found between the duration of Paralympic training and the number of injuries and rehabilitation sessions (R = -0.4; P < .02) and between the exclusion from training for less 4 and over 4 weeks (R = -0.4; P < .03). The age of the Para athletes correlated with the NMQ-7 (wrists) (R = 0.4; P < .01). Both duration of disability and the type and severity of the disability may be crucial determinants of the prevalence and location of pain in the musculoskeletal system in Para athletes. Sport-specific training seems to induce specific musculoskeletal complaints.